A chemist's overview of surface electron spins. (20th March 2017) - Huang, Zhichao; Zhang, Yajie; He, Yang; Song, Huanjun; Yin, Cen; Wu, Kai
Abstract : Tuning surface electron spins with chemical approaches and systems. Abstract : This review summarizes recent research progress in the measurement and tuning of the electron spins of alien atoms and molecules adsorbed on well-defined substrates. After a brief introduction to the main experimental techniques employed to study surface electron spins, some well-explored systems consisting of atomic and molecular spin-carriers at surfaces are overviewed from a chemist's viewpoint, focusing on the experimental measurements and chemical modifications of the electron spin states of the alien entities at the surfaces on the atomic/molecular level. Finally, personal perspectives have been provided, aiming at describing some of the remaining issues that need to be addressed in the future and proposing potential applications in surface chemistry.